2011
DOI: 10.1038/pcan.2010.54
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase gene polymorphisms (GSTM1, GSTT1, GSTP1) and prostate cancer: a case-control study in Tehran, Iran

Abstract: We evaluated the relationship between polymorphisms in the glutathione S-transferases (GSTs) GSTM1, GSTT1 and GSTP1 genes and prostate cancer (PCa). PCR-restriction fragment length polymorphism assay was used to genotype the GSTM1, GSTT1, and GSTP1 polymorphisms in 168 PCa cases and 336 frequency matched controls. The GSTM1 null, and GSTT1 null genotypes were associated with an increased odds ratio (OR) for PCa (OR ¼ 3.28, 95% confidence interval (CI): 2.47-5.64; P ¼ 0.005, and OR ¼ 3.21, 95% CI: 2.52-5.64; P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
(68 reference statements)
3
30
1
Order By: Relevance
“…17,18 A more recent study also demonstrated that GSTM1 null and GSTT1 null genotype was observed in a higher frequency in patients with a Gleason score >7. 19 A detailed analysis of GST gene polymorphisms and their association with clinicopathological parameters in prostatectomy specimens does not exist in our population. Therefore, whether these genes have prognostic impact on prostate cancer patients remains unknown for Turkish men.…”
Section: Discussionmentioning
confidence: 92%
“…17,18 A more recent study also demonstrated that GSTM1 null and GSTT1 null genotype was observed in a higher frequency in patients with a Gleason score >7. 19 A detailed analysis of GST gene polymorphisms and their association with clinicopathological parameters in prostatectomy specimens does not exist in our population. Therefore, whether these genes have prognostic impact on prostate cancer patients remains unknown for Turkish men.…”
Section: Discussionmentioning
confidence: 92%
“…Of these studies, 9 reported on Caucasians, and 9 reported on East Asians. Studies were carried out in Japan (Murata et al, 2001;Nakazato et al, 2003;Komiya et al, 2005), China (Guan et al, 2005;Lai et al, 2005;Wang et al, 2005;Yang et al, 2006;Li et al, 2008), India ( Vijayalakshmi et al, 2005;Srivastava et al, 2005;Mittal et al, 2006;Thakur et al, 2011;Kumar et al, 2011), South Korea (Kwon et al, 2011), Iran (Ashtiani et al, 2011;Safarinejad et al, 2011) and Turkey (Aktas et al, 2004;Silig et al, 2006). A list of details abstracted from the studies included in the meta-analysis is provided through Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…GSTP1 Ile105Val polymorphism modifies the kinetic properties of coded enzyme (16,17) and some other studies demonstrated higher sensibility for carcinomas in individuals bearing the variant valine allele (18).…”
mentioning
confidence: 91%